A probabilistic manifestation for the assessment of structural behaviour and understanding professional ethics: A multi- dimensional approach. - Eusuf, Muhammad Abu; Salleh, Md. Noor (2018)
It is desirable to verify the structural performance (SP) based on a multi-dimensional approach, considering the significant actions the structure in issue could be subjected to during its lifecycle assessment. The whole lifetime principle has been familiarized keen to analysis, design and management of structures. The professional have to regenerate and study novel skills in order to achieve a capability for life sequence on design and predictive or service life management of any type of structure from low rise to high rise and short span to long span. The novel skills include new approach for analysis, design and management process, durability, performance, service life of materials and structures, reliable methods of computation for control the safety over the service life of structures. Although this reliable method is time dependent and treated as time dependent parameters. For this reason safety margin should maintain effectiveness for total life cycle in order to depend the cost of maintenance works and capitalize the performance and serviceability of the structures. Structural failures occur on the basis of time, professionals are not made any aware of this failure in their analysis, design and management process. The authors are approaching to include all provisions include reporting system of failures, causes of failures, detailing of failures- illustrated with free body diagrams, detailing through analytical advancement in their new reliable methods. Our hypothesis is that studying specific structural failures has a positive impact on professional’s wisdom and experiences. Which is, in turn shows the ethical endorsement of professionalism. This study has demonstrated a proposal for the assessment of structural behaviour in multi-dimensional approach, emerge with professional ethics leading to the sustainable approach in application and implantation area.